The Role of Maternal and Infant Diet in the Management of Infantile Colic: A Comprehensive Review - Paruzel, Marcel; Łęcka, Martyna; Żak, Katarzyna; Załóg, Adam; Nowak, Maria; Pietryszak, Edyta; Kulej, Wojciech; Szołtek, Paulina; Pardela, Rafał; Wojtasik, Monika (Journal of Education, Health and Sport, 2025)
This systematic review aims to determine the effects of maternal and infant diet on the incidence and treatment of infant colic with emphasis on dietary modifications and its potential to reduce the symptoms. The role of maternal and infant diet on psychological health of the mother and breastfeeding practices as risk factors in reducing the frequency of colic episodes has been highlighted. The role of maternal gut microbiota composition especially the bacterial enterotypes has been discussed with relation to colic. Also, the efficacy of probiotics especially the Lactobacillus reuteri strains has been evaluated with variable results depending upon the strain and the dose used. The review discusses how the definitions and criteria used, for instance Wessel and Rome IV, influence the perception of incidence and nature of colic. It also includes descriptive content analysis of various researches where cultural and socio-economic factors including maternal empowerment in different contexts are discussed in relation to the management plans. The analysis of meta-analysis and risk of bias studies enhances the conclusions and offers practical recommendations on dietary interventions. The present study reveals that the personalized dietary approaches are effective and at the same time points out the need to fill the research gaps in order to provide better solutions for parents of colicky infants.